Village Government Strategy In Managing Village-Owned Enterprises (Bumdes) In Batu Kotam Village, Lamandau District: STRATEGI PEMERINTAH DESA DALAM MENGELOLA BADAN USAHA MILIK DESA (BUMDES) DI DESA BATU KOTAM KABUPATEN LAMANDAU - Pratama, Muhammad Anzarach (Pencerah Publik, 2022)
This study aims to identify internal and external environmental factors and analyze management strategies that influence the utilization of assets in the development of the Village-Owned Enterprise (BUMDes) Batu Kotam in Lamandau Regency. The method used is qualitative-descriptive, with primary data collected through observation, interviews, and documentation. The data were analyzed through the processes of reduction, presentation, and conclusion drawing. This research also employs the Internal-External (IE) matrix analysis to determine the position of the BUMDes and the SWOT (Strengths, Weaknesses, Opportunities, Threats) matrix to formulate development strategies. The results indicate that optimal management strategies include enhancing internal competitiveness, conducting comparative studies with other BUMDes enterprises, identifying community needs, providing management and information technology training for administrators, recruiting voluntary administrators, educating the community about BUMDes, collaborating with local entrepreneurs, improving management, increasing human resource competencies through training, optimizing capital, and implementing continuous evaluation and control. These strategies are expected to effectively support the sustainability and independence of BUMDes Batu Kotam.